Kebutuhan Lahan Kopi Minimum untuk Kesejahteraan Petani di Provinsi Lampung - Baiq Rindang Aprildahani; Nela Agustin Kurnianingsih; Marsista Buana Putri; Annisa Aprilia (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Indonesia, which is known to be an agricultural country and as one of the largest coffee exporters in the world, still has problems with the welfare of farmers. Decreased in agricultural land area can threaten the welfare of farmers. This is one of the concerns of this study by taking a case study of the welfare of coffee farmers in Lampung. This study aims to identify the need for a minimum coffee land area to maintain the stability of the welfare of coffee farmers in Lampung. This research will be conducted using qualitative descriptive research methods to examine efforts in the welfare of coffee plantation farmers, through its key factor, namely land ownership. The research process was carried out by identifying the results of calculating the production value and cost of coffee production in Lampung, which was then continued by calculating the level of welfare of the coffee farming community in order to get the final result of calculating the minimum coffee land area in Lampung. Based on the calculation results, each coffee farmer in Lampung Province needs an average of 4.06 hectares to meet the welfare according to the resident minimum wage. Meanwhile, based on the 2020-2022 National Leading Plantation Statistics, the average land area owned by coffee farmers in Lampung Province is still far from the need to fulfill the welfare of these farmers, which only reaches 27% (1.1 Ha).